2020
DOI: 10.1101/2020.10.29.360503
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-biasedZRSR2mutations in myeloid malignancies impair plasmacytoid dendritic cell activation and apoptosis

Abstract: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is an aggressive leukemia of plasmacytoid dendritic cells (pDCs). BPDCN occurs at least three times more frequently in men than women, but the reasons for this sex bias are unknown. Here, studying genomics of primary BPDCN and modeling disease-associated mutations, we link acquired alterations in RNA splicing to abnormal pDC development and inflammatory response through Toll-like receptors. Loss-of-function mutations in ZRSR2, an X chromosome gene encoding a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 69 publications
(85 reference statements)
0
37
0
Order By: Relevance
“…Summerer et al [ 28 ] analyzed 1367 mutations in 1210 genes in 21 BPDCN cases and found mutations in SRSF2 in 7 (33%), SF3B1 in 2 (10%), U2AF1 in 2 (10%), and ZRSR2 in 2 (10%) cases. Loss-of-function mutations in ZRSR2 have been shown to impair plasmacytoid dendritic cell activation and apoptosis after inflammatory stimuli, thus may impair immunity and predispose to leukemic transformation [ 29 ]. The presence of frequent mutations of RNA splicing factor may result in impairment of RNA splicing and defective assembly of gene transcripts, which could contribute, at least in part, to the disruption of signaling pathways involved in plasmacytoid dendritic cell maturation and thus BPDCN tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Summerer et al [ 28 ] analyzed 1367 mutations in 1210 genes in 21 BPDCN cases and found mutations in SRSF2 in 7 (33%), SF3B1 in 2 (10%), U2AF1 in 2 (10%), and ZRSR2 in 2 (10%) cases. Loss-of-function mutations in ZRSR2 have been shown to impair plasmacytoid dendritic cell activation and apoptosis after inflammatory stimuli, thus may impair immunity and predispose to leukemic transformation [ 29 ]. The presence of frequent mutations of RNA splicing factor may result in impairment of RNA splicing and defective assembly of gene transcripts, which could contribute, at least in part, to the disruption of signaling pathways involved in plasmacytoid dendritic cell maturation and thus BPDCN tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Yoshida et al demonstrated that nonsense or frameshift mutations in ZRSR2 causing either a premature truncation or a large structural change of the protein, leading to loss-of-function are found exclusively among men and not women [ 42 ]. More recently in a pre-print, Togami et al reported that loss-of-function ZRSR2 mutations are enriched in blastic plasmacytoid dendritic cell neoplasm, a rare leukemia with a three times higher incidence among men and almost all these mutations occur in men [ 43 ].…”
Section: Hypothesized Biologic Mechanisms Implicated In the Gendermentioning
confidence: 99%
“…In this study, we observe increased expression of IFNA response genes in T-cells relative to Tcells in the healthy controls, initially suggesting higher levels of IFNA production by pDC-like tumor cells. However, previous research on BPDCN has shown that pDC-like tumor cells produce lower levels of IFNA relative to pDCs from healthy individuals (44,45). Further, little research has been reported describing the role of TNFA signaling in BPDCN, though studies have shown increased TNFA signaling in the plasma of patients with acute myeloid leukemia (46,47).…”
Section: Discussionmentioning
confidence: 99%